Pemberian Beberapa Jenis Dan Konsentrasi Auksin Untuk Menginduksi Perakaran Pada Stek Pucuk Bayur (Pterospermum javanicum Jungh.) Dalam Upaya Perbanyakan Tanaman Revegetasi - Agusti Apriliani; Zozy Aneloi Noli; Suwirmen Suwirmen (Jurnal Biologi Universitas Andalas, 2015)
The research on effect of types and concentration of auxin on root induction of apical shoots Bayur (Pterospermum javanicum jungh.) in attempt to propagate of revegetation plants was conducted from May to August 2015 in the Nursery and Greening of Andalas University, and Laboratory of Plant Physiology Department of Biology, Faculty of Mathematics and Natural Sciences, Andalas University. The aimed to know the response of apical shoots Bayur (P. javanicum) on  root induction by providing some type and concentration of Auxin. This research used method of Complete Randomized Design (CRD) with seven treatments and three replications. The treatments consist of control, IBA 100 ppm, IBA 200 ppm, NAA 100 ppm, NAA 200 ppm, IAA 100 ppm, IAA 200 ppm. The result of this study showed that there was no respons of any treatments in inducing root of  apical shoots of Bayur (P. javanicum).Keywords: Auxin, Pterospermum javanicum, revegetation, root induction